International approaches to bridging the language gap - Huertas-Abril, Cristina A., 1987-; Gómez-Parra, M. Elena, 1970- (Advances in linguistics and communication studies (ALCS) book series., 2020)
"This book explores methods and applications of second language teaching as well as social developments regarding intercultural learning"--Provided by publisher.